Towards the Expert Governance: Social Scientific Expertise and the Socialist State in Czechoslovakia, 1950s–1980s - Sommer, Vítězslav (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
This article is concerned with the process of introduction and the further expansion of social scientific expertise in state socialist Czechoslovakia from the mid-1950s until 1989. It presents these developments in the context of the changing policy strategies of the Communist Party elites and describes how closely social scientific expertise, and social scientific knowledge production in general, was interconnected with the broader development of the state socialist governance from the post-Stalinism of the second half of the 1950s to the 1980s perestroika period. This text is structured around three crucial realms of the state socialist governance: state, economy and labor, and socialist society. The first part of the article is concerned with the expertise in the field of state, law and political sciences, which played a significant role during the late 1950s, when the socialist statebuilding project was finished. The following section focuses on the rise of social scientific expert culture during the reform communist period of the 1960s. The third part of this study analyzes how the reform communist expert culture was transformed by the post-1968 regime in a large expert apparatus in order to build strictly centralized technocratic governance. Finally, this article describes how social scientific expertise responded to the crisis and disorganization of state socialist governance during the perestroika period.